(3GdShb GdGaQjbjI GdeTJQcI hGdEJMGO GdGaQjbis - (3YHO GdMejO(B, (3YHO GdeWdHs ((3GdbGgQIs (3eLehYI Gdfjd GdYQHjIs, 2004)
(3aj Xd fXGe GbJUGOj YGdej LOjO, dG jYJQa EdG HGdcjGfGJ GdcHjQI, hdG ecGf ajg ddcjGfGJ GdUZjQI GdeJaQbI, CUHM ef GdVQhQj hef GdMJej Cf JJLg GdOhd GdEaQjbjI Edi Jchjf JcJd GbJUGOj EaQjbj, jfbP EaQjbjG ef eTcdGJgG hjbjdgG ef YKQJgG, NGUI Cf EaQjbjG gj GdbGQI GdCZfi ef MjK GdehGQO GdGbJUGOjI hJhGaQgG, hGdCabQ ef MjK GSJZdGd hEOGQI gPg GdehGQO, GdCeQ GdPj jMJe Ydi GdOhd GdEaQjbjI Cf Jcnqhf gPG GdcjGf GdGbJUGOj GdJcGedj, GdPj ojnMqSf GSJNOGe gPg GdehGQO aj eLehYgG dJYhO HGdNjQ hGdfeGA Ydi cd Ohd gPg GdbGQI GdSeQGA PGJ GdCZdHjI GdabjQI(B. (3hef GdedGMX Cf gfGc LghkOG cHjQI bO oHPdJ efP MUhd GdOhd GdEaQjbjI GdKdGK hGdNeSjf Ydi GSJbdGdgG, ef CLd Jchjf eLehYI ef GdJcJdGJ GdGbJUGOjI, PGJ GdoHYO GdLZQGaj GdEbdjej, hGdJj JJTGHg aj XQhagG GdGbJUGOjI, CedkG aj Jchjf eG jecf Cf ojWdb Ydjg GdLeGYI GdEaQjbjI hUhdkG HgG Edi GdShb GdEaQjbjI GdeTJQcI, Ydi ZQGQ GdLeGYI GdGbJUGOjI GdChQhHjI, hGdJj JMhdJ ajeG HYO Edi GdGJMGO GdChQhHj(B. (3hdPdc jMGhd gPG GdcJGH YQV GdJLQHI GdEaQjbjI ef NdGd JfGhd GdShb GdEaQjbjI GdeTJQcI dOhd LfhH hTQb EaQjbjG hGdGJMGO GdEaQjbj hBaGbg GdeSJbHdjI hJLO aj WjGJg eGjdj ef aUhd (B1.(3GdShb GdEaQjbjI GdeTJQcI hGdEJMGO GdEaQjbj (B2.(3GdJYQja HGdShb GdYQHjI GdeTJQcI (B3.(3GdGWGQ GdeDSSj ddShb GdEJMGO GdEaQjbj GdeTJQc (B4.(3GdedGeM GdGSGSjI dGbJUGOjGJ Ohd GdShb GdGaQjbjI GdeTJQcI (B5. (3eLGdGJ GdJYGhf GdGbJUGOj Hjf Ohd GdShb GdGaQjbjI GdeTJQcI (B6.(3eDJeQGJ GdShb GdGaQjbjI GdeTJQcI hfJGFLgG (B7.(3GHYGO hGaGb GdYdGbGJ GdGbJUGOjI Hjf eUQ hGdShb GdGaQjbjI GdeTJQcI (B8.(3GdGJMGO GdGaQjbj hBaGbg GdeSJbHdjIs
Keywords: (3GdGbJUGO GdOhdjs; (3GdGbJUGO(B-(3Ohd GaQjbjG s